ANALISA BAHAYA DENGAN METODE JOB SAFETY ANALYSIS (JSA) PADA PEKERJAAN STRINGING SUBKONTRAKTOR PLN PROYEK REKONDUKTORING SUTT 150 KV TANJUNG-JATI - Charisha Mahda Kumala; Yoga Adhi Dana (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
PLN workers are in an unsafe condition where they use energized equipment or conductors. In electrical construction projects at PLN, the use of Job Safety Analysis (JSA) facilitates the identification of hazards and risk assessment. The purpose of the study presented in this research is to investigate the practices and benefits of JSA in a case study of electrical construction projects where the level of hazards and risks is greater than other construction projects. In electrical construction projects at PLN, the use of JSA facilitates the identification of hazards and risk assessment. The objective of the study presented in this research is to investigate the practices and benefits of JSA in a case study of electrical construction projects where the level of hazards and risks is greater than other construction projects. The research model employs a qualitative approach to investigate the practices and benefits of JSA in the construction industry during electrical work processes. The qualitative study consists of interviews with workers, direct observation of the work processes at PLN's 150 kV Tanjung-Jati re-conductoring SUTT project, and analysis of work documents. JSA in PLN construction work is useful for facilitating the identification of hazards and risks. Safety briefings can be conducted to remind workers about the hazards and risks they face and provide instructions according to work procedures and proper use of personal protective equipment (PPE).